Methods of Forecasting Wear Resistance of Cutting Tools Based on the Properties of their Materials; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Bibik V. L. Vladislav Leonidovich (2014, 2014)
Title screen